2017
DOI: 10.3892/ol.2017.6460
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential key genes associated with glioblastoma based on the gene expression profile

Abstract: Gliomas are serious primary brain tumors. The aim of the present study was to identify potential key genes associated with the progression of gliomas. The GSE31262 gene expression profile data, which included 9 glioblastoma stem cells (GSCs) samples and 5 neural stem cell samples from adult humans, were downloaded from Gene Expression Omnibus (GEO) database. limma package was used to identify differentially expressed genes (DEGs). Based on STRING database and Pearson Correlation Coefficient (PCC), a co-express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…By querying the public TCGA stomach adenocarcinoma sequencing data, 78 genes were implicated possibly being co-expressed with cyclin E. Pearson correlation coefficient evaluation of the correlation between the co-expression of these genes and cyclin E used a coefficient threshold set at 0.4. 19 , 20 The 78 genes included 5 non-coding genes ( LOC642852 , PHF2P1 , BAIAP2-AS1 , CSNK1A1P1 , and MIMT1 ). These non-coding genes and their transcripts (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By querying the public TCGA stomach adenocarcinoma sequencing data, 78 genes were implicated possibly being co-expressed with cyclin E. Pearson correlation coefficient evaluation of the correlation between the co-expression of these genes and cyclin E used a coefficient threshold set at 0.4. 19 , 20 The 78 genes included 5 non-coding genes ( LOC642852 , PHF2P1 , BAIAP2-AS1 , CSNK1A1P1 , and MIMT1 ). These non-coding genes and their transcripts (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This study sought to identify genes potentially co-expressed with the cyclin E oncogene in gastric cancer and to clarify the probable regulatory mechanisms. By querying the public TCGA stomach adenocarcinoma sequencing data, 78 genes were implicated possibly being co-expressed with cyclin E. Pearson correlation coefficient evaluation of the correlation between the co-expression of these genes and cyclin E used a coefficient threshold set at 0.4 19, 20. The 78 genes included 5 non-coding genes ( LOC642852 , PHF2P1 , BAIAP2-AS1 , CSNK1A1P1 , and MIMT1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, no subtypespecific genetic signature was found [64]. There are also a number of other research papers devoted to the study of the molecular characteristics of one or two types of glial tumours [65][66][67]. Our study is characterized by a large number of samples and tumour subtypes (939 samples of 5 different subtypes of gliomas were analysed) and an integrative approach, which consists in the analysis of signalling pathways, survival and the search for subtype-specific markers among DEGs and DE miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…With the help of gene microarray and RNA-seq, the aberrant expression profiles of GBM in genome and transcriptome level were increasing reported. Using the gene expression data from Gene Expression Omnibus (GEO) database, Bo et al [6] identified a total of 431 differentially expressed genes (DEGs) between GBM and normal samples. After various bioinformatics analysis, 69 DEGs were identified significantly associated with GBM prognosis.…”
Section: Introductionmentioning
confidence: 99%